CHALLENGES IN TEACHING FOREIGN LANGUAGES INTENSIVELY TO ADULT LEARNERS AND THEIR SOLUTIONS (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
The growing demand for intensive foreign language instruction among adult learners has led to the need for more effective teaching strategies tailored to this specific group. Adult learners differ significantly from younger learners in cognitive, psychological, and social dimensions, which influences their ability to acquire a new language, especially under intensive conditions. This paper examines the key challenges in teaching foreign languages intensively to adults, including cognitive overload, psychological barriers, time constraints, and heterogeneity of learner backgrounds. It also proposes practical solutions grounded in modern pedagogical approaches such as communicative language teaching, task-based learning, and technology-enhanced instruction. The study concludes that a learner-centered and flexible approach is essential for successful intensive language teaching.